Rola asystenta rodziny w aktualnej rzeczywistości. - Walancik, Karolina (Studia Edukacyjne, 2026)
This article addresses issues related to the role of the family assistant. The author discusses and describes the tasks of the family assistant. She presents the results of empirical research on the functioning of the family assistant in the current reality, in the face of the crisis of the family institution, the post-pandemic period, the war in Ukraine, multiculturalism, and the labor emigration of Poles.